Urban Transportation Problems in Basra and Ways to Address Them - Asist. Lect. Zainab Ahmed Jassim (Journal of College of Education, 2026)
This research examines urban transport in Basra, presenting its historical development, resources, challenges, and proposed solutions for its improvement. Urban transport is a fundamental element in supporting urban, social, and economic development, and it reflects the quality of life in the city. Despite the expansion of road networks after 2003, this expansion was not linked to a clear urban vision. Consequently, numerous problems emerged, most notably the weak enforcement of traffic laws and the unregulated spread of private vehicles, resulting in traffic congestion and environmental and service-related impacts. The research adopted a descriptive-analytical approach, utilizing statistical data and spatial maps to monitor transport patterns and diagnose field problems. The results showed that the urban transport crisis in Basra is not only related to infrastructure deficiencies but also to the absence of clear traffic policies and the high reliance on private cars. The research recommends developing the public transport system, supporting it with scientific options, and adopting intelligent traffic management technologies to contribute to regulating traffic flow and improving transport efficiency within Basra
Keywords: Urban transport problems in Basra, and ways to address them